The Globalization of theological education - "Evans, Alice Frazer"; "Evans, Robert A.;Roozen, David A." ("Maryknoll, N.Y. :")
Includes bibliographical references and index
Keywords: "THEOLOGY - STUDY AND TEACHING;CHRISTIANITY AND CULTURE;MISSIONS - THEORY;CHRISTIAN UNION;EVANS, ALICE F.;EVANS, ROBERT A. 1937-;ROOZEN, DAVID A."